A wnt2 ortholog in the sea urchin Paracentrotus lividus. Issue 11 (3rd September 2019) - Robert, Nicolas; Hammami, Firas; Lhomond, Guy; Dru, Philippe; Lepage, Thierry; Schubert, Michael; Croce, Jenifer C.
Summary: Members of the wnt gene family encode secreted glycoproteins that mediate critical intercellular communications in metazoans. Large‐scale genome and transcriptome analyses have shown that this family is composed of 13 distinct subfamilies. These analyses have further established that the number of wnt genes per subfamily varies significantly between metazoan phyla, highlighting that gene duplication and gene loss events have shaped the complements of wnt genes during evolution. In sea urchins, for example, previous work reported the absence of representatives of both the WNT2 and WNT11 subfamilies in two different species, Paracentrotus lividus and Strongylocentrotus purpuratus . Recently, however, we identified a gene encoding a WNT2 ortholog in P. lividus and, based on that finding, we also reanalyzed the genome of S. purpuratus . Yet, we found no evidence of a bona fide wnt2 gene in S. purpuratus . Furthermore, we established that the P. lividus wnt2 gene is selectively expressed in vegetal tissues during embryogenesis, in a pattern that is similar, although not identical, to that of other P. lividus wnt genes. Taken together, this study amends previous work on the P. lividus wnt complement and reveals an unexpected variation in the number of wnt genes between closely related sea urchin species.